Racionalidades tecnoburocráticas e quilombolas: integração da comunidade Córregos das Moças ao PAA - Coradin, Cristiane (2014)
This study aims to understand how the bureaucratic rationality of the Food Acquisition Program (PAA) me relates to the rationality of the Maroons Community Córrego das Moças , located in the city of Adrianópolis - PR. For both qualitative research performed under an ethnographic perspective, associated with literature about the subject. As results, analyze the social integration of these subjects to the PAA has generated subtle changes in their production systems, contemplating some changes in the social divisions of family work, providing increased autonomy of women and youth against husbands and fathers. Collectively, the bureaucratic integration of the group program sustains itself, redefining and reinforcing, reciprocal relationships, friendship and kinship, patron-client relationships and male domination present in the group. I realized that the assimilation of the group to the standards of regulation , standardization , routinization and formalization of accountings of the program has been going conflictive , asymmetrical and conditional , so in some cases , suffering internal adjustments and adaptations , and in other cases not being fully knowable to those subjects. In these contexts, professional mediators and Maroons have completed significant role in connecting worldviews and ethos, establishing itself as a specialized technical body. This scenario, however, has blocked the assumption, control, socialization and participants Maroons, which remains subject to the mediators responsible for managing the learning design. Finally, I analyze the integration process of the Maroons PAA has promoted the expansion of its relative autonomy, in that it describes the condition of the peasant participants, families locked, however, the assumption, material and symbolic appropriation of dynamic tecnoburocráticas by Maroons in project management, constraining options for expanding relative autonomy and ethnogenesis of the group process, reproducing contexts of violence and legal and symbolic domination. Conclude the study indicates the need for connection between facing the peasant agriculture, family and maroon, with public policies promoting racial equality as a condition necessary for the full development of these ethnic groups public policy.